A dimensão da espiritualidade como estratégia de enfrentamento no diagnóstico positivo de HIV/AIDS em gestantes. - Pereira, Rita de Cássia de Carvalho (2010)
This study wished to analyse the dimension of spirituality as a confrontation strategy used by pregnant women attended in the Maternal and Child Specialized Care Service- SAE/MI in face of seropositive diagnosis for HIV/AIDS, of University Hospital Lauro Wanderley- HULW of Joao Pessoa, in Federal University of Paraíba. This is a descriptive and exploratory research, case study type, with a sample of 08 infected pregnant women who found the diagnosis of HIV/AIDS during prenatal care. It were used as instruments for data collection a script of semi-structured interviews, containing 09 questions that examined the impact of seropositive diagnosis for HIV/AIDS, including biodemographic issues and a questionnaire comprising two scales: Scale of Religiosity and health problem confrontation and scale of satisfaction with life and spirituality. Data analysis of interviews was conducted by Thematic Content Analysis of Bardin (1977) and the questionnaire was treated by the statistical package SPSS (Statistics Package for Social Sciences) version 16.0. The results obtained showed that 87.5% of infected pregnant women come from a stable union and attended incomplete elementary school; 75% presented themselves as Catholic, 37.5% found the diagnosis in late pregnancy (08 months). It was also observed that 75% affirmed private religious practices in their quotidian; where praying, orating and praising were identified as those most frequent by pregnant women, and that 75% of them agree that going to church/Center/Meeting/Temple influenced them to change concepts and practices in their lives. In the analysis of the interviews with pregnant women, seven categories emerged that addressed different issues, they are: 1) Knowledge about HIV/AIDS, 2) Feeling towards the discovery of HIV/AIDS, 3) Current feeling, 4) Relation of family with the pregnant woman diagnosis, 5) Current Concerns, 6) Confrontation of HIV/AIDS and 7) Beliefs about themselves before diagnosis. It is noteworthy that some categories are subdivided further into subcategories. It was observed that the speech of the pregnant women represented on one hand, the knowledge about HIV/AIDS; and, on the other hand, the lack of knowledge of the disease. The pregnant women showed predominantly negative emotions as well as exposed opposition of feelings towards the acceptance of positive diagnosis for HIV/AIDS. Although, otherwise appears pregnant women who complied with the diagnosis for HIV. They showed the involvement and family support to the pregnant woman at the moment of seropositive diagnosis for HIV/AIDS; In many cases the disclosure of diagnosis is feared by the pregnant woman; It were observed apprehensions involving, in the first place, the concern about the baby and anguish about herself and her seropositive status and about the care of the family; Due to the variety of support elements used by seropositive pregnant women, this category was divided into sub-categories "Religious Support," "Family Support", "Support of SAE/MI Health Team" and "Other supports". Regarding beliefs of pregnant women about themselves before diagnosis, they showed positive beliefs sufficiently strong; The negative beliefs about themselves before diagnosis, some pregnant women appeared to present a previous life of hardship. The results allowed to achieve that there was a contribution of the spirituality dimension as a confrontation factor of the impact of diagnosis of HIV/AIDS in these pregnant women. We conclude that the majority of women surveyed cited the importance of spiritual well-being as a contribution to the confrontation of HIV / AIDS diagnosis discovered in their gestation.